Reading bridal magazines from a critical discursive perspective - Glapka, Ewa; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2014)
Offering a critique of contemporary wedding discourse, this book marries together analyses of media texts and their reception to propose a new approach to media discourse. The analysis richly illustrates how women are invited to embrace not only the stereotypical idea of bridal femininity but also a consumptive way of experiencing it.
Keywords: Social sciences; Culture -- Study and teaching; Communication; Sociolinguistics; Discourse analysis; Sociology; Cultural studies; Sex (Psychology).; Gender expression; Gender identity; Social Sciences; Gender Studies; Discourse Analysis; Sociolinguistics; Cultural and Media Studies, general; Media Studies; Cultural Studies